PENGARUH KOMPETENSI GURU BAHASA ARAB DAN MINAT BELAJAR SISWA TERHADAP HASIL BELAJAR BAHASA ARAB SISWA KELAS IX MTS DI KECAMATAN KEBAYORAN LAMA - NENENG LM (Sekretariat Badan Litbang dan Diklat Kementerian Agama RI, 2017)
This study aims at determining the factors that influence students’ learning outcomes by examining the effect of Arabic teacher competence and students’ interest in learning Arabic towards students’ outcomes of Grade IX MTs (Islamic Junior High Schools) in Kebayoran Lama subditrict. The study finds out that: first, there is a direct and significant influence of the high competence of teachers on students’ Arabic learning outcomes. Secondly, there is a positive and significant effect of teacher competence on student interest. Thirdly, by the value of þ32 = 0.46> 0, the regression equation X3 = -6.866 + 0,264X2, the correlation coefficient r23 = 0.785 and determination coefficient r23 = 0.617, or 61.70% it can be inferred that there is a direct and significant influence of students’ learning interest to their Arabic learning outcomes. These findings imply that obtaining good outcome in students’ Arabic learning can be done by improving the competence of teachers and students’ interest in learning. KEY WORDS: Teacher Competence, Learning Interest, Learning Outcomes, Islamic Junior High School